Heart transplantation in neonates and children. Intermediate-term results - Azeka,Estela (2000)
OBJECTIVE: To assess intermediate-term outcome in children who have undergone orthotopic heart transplantation. METHODS: We carried out a longitudinal and prospective study between October '92 and June '99 comprising 20 patients with ages ranging from 12 days to 7 years (mean of 2.8 years). We employed a double immunosuppression protocol with cyclosporine and azathioprine and induction therapy with polyclonal antithymocyte serum. Survival and complications resulting from the immunosuppression protocol were analyzed. RESULTS:The double immunosuppression protocol and the induction therapy with polyclonal antithymocyte serum resulted in an actuarial survival curve of 90% and 78.2% at 1 and 6 years, respectively, with a mean follow-up period of 3.6 years. One patient died due to acute rejection 40 days after transplantation; another patient died 2 years after transplantation due to lymphoproliferative disorder; a third patient died because of primary failure of the graft; and a fourth patient died due to bronchopneumonia. The major complications were as follows: acute rejection, infection, nephrotoxicity, and systemic hypertension. The means of rejection and infection episodes per patient were 2.9 and 3.4, respectively. After one year of transplantation, a slight reduction in the creatinine clearance and systemic hypertension were observed in 7 (38.9%) patients. CONCLUSION: Heart transplantation made life possible for those patients with complex congenital heart diseases and cardiomyopathies in refractory congestive heart failure constituting a therapeutical option for this group of patients in the terminal phase.